Peran Mahasiswa dalam Menghadapi Pembungkaman Pers pada Masa Rezim Orde Baru, 1974-1998 - Sophianti, Naia (Forum for Social and Humanities Studies, 2025)
This article examines the role of Indonesian students in confronting the New Order regime (1974-1998), a period marked by political, economic, and social crises following the military takeover. The historical backdrop reflects widespread dissatisfaction that culminated in the Malari incident of 1974, a pivotal moment in the students' struggle for freedom of expression and the press. Student protests not only articulated grievances against government policies but also led to media crackdowns, exemplified by the case of Harian KAMI, which highlighted government efforts to silence critical voices. In the face of repression, students adapted by creating alternative media and forging alliances with various organizations, thus strengthening the social movement. This article also explores how student protests and public discussions successfully fostered public opinion in support of reform. By analyzing the impact of student activism, the article underscores their crucial role in cultivating collective awareness and promoting the transition towards the reform era. In conclusion, student voices, despite being stifled in various ways, remained a significant force in opposing authoritarian regimes, emphasizing the importance of active participation in the democratic struggle in Indonesia.